Solusi Alternatif Spin-Off Premature Bagi Unit Usaha Syariah Di Indonesia - Laila Afni Rambe (IAIN Langsa, 2021)
Expectations of increased development of Islamic banking is one of the targets by the government in the year 2023. To achieve this target in recent years, the government conducted a roadmap by requiring all Islamic business units that are in conventional commercial banks to separate themselves. So that every sharia business unit will turn into a sharia commercial bank. It becomes a challenge for every UUS in facing spin-offs, especially in preparing a large amount of capital. Therefore, many UUS are not ready financially for spinoffs. So the solution offered by the author can be in the form of a review of Law Number 21 Year 2008 concerning Sharia Banking which is the legal basis for the spin-off policy. In addition, BUK needs to prepare the maturity of UUS to face separation. Without exception the preparation of the UUS itself in improving services and the addition of banking products offered. Besides that, education is also very important to educate the public.